Debunking neuromyth in education: what is the fact and what is fiction for Malaysia teachers? - Muhammad Syawal Amran; Sommer, Werner (Penerbit Universiti Kebangsaan Malaysia, 2024)
Research in Neuroscience and Education aims to bridge the gap between education, neuroscience and cognition. However, numerous challenges continue to hinder the integration between education and neuroscience, such as neuromyth in education. The main aim of this study was to verify whether Malaysian teacher is susceptible to misconceptions about neuroscientifi c fi ndings that impair their teaching. An online survey was conducted among (n =501) school teachers, covering 14 neuro facts and four neuro fi ction about the brain. Results show 82.2% of participants believe the diff erences between the left brain and right brain can help explain individual diff erences amongst learners, and 89.2% of participants believe that ‘Individuals learn better when they receive Information in their preferred learning style (e.g., auditory, visual, kinesthetics). For the neuro facts, 83.6% of teachers correctly classifi ed ‘There are sensitive periods in childhood when it’s easier to learn things’, and 79.2 % responded correctly to ‘Information is stored in the brain in a network of cells distributed throughout the brain. Our fi ndings show the importance of improved interdisciplinary communication to prevent such misconceptions and foster eff ective collaboration between neuroscience and education in the future.